Dimensi moral dalam kekuasaan politik - Muchson AR (Universitas Negeri Yogyakarta, 2004)
The oldest legitimation of authority is religious legitimation, a doctrine of the Middle Ages. The King is believed as the figure manifested of God authority. like the religious concept, the Javanese mystical concepts believe that the King authority comes from the supernatural power, not from people support. Although that opinion is considered as religious legitimation, but Islam is not like it. The Holy Qur'an more emphasizes for justice and morality in political system. In the Javanese mystical perception, King is looked as a microcosm who can reserves the power of a macrocosm and then emanates it. The King's character should indicate natural power, such as power of the sun, moon, star, etc. The other side of harmony with whole world, the King must be able to create a social harmony. Political ethics in democracy political system based on Pancasila also emphasizes that the legitimation of authority comes from people mandate, as a principle of democracy. Even though, the authority's moral and moral responsibility of authority must be appreciated and respected. The opinion that authority is not a moral legitimation and the authority is not personification of moral goodness should be rejected